\(x:\dfrac{4}{7}=\dfrac{6}{7}-\dfrac{1}{3}\\ \Rightarrow x:\dfrac{4}{7}=\dfrac{18}{21}-\dfrac{7}{21}\\ \Rightarrow x:\dfrac{4}{7}=\dfrac{11}{21}\\ \Rightarrow x=\dfrac{11}{21}\times\dfrac{4}{7}\\ \Rightarrow x=\dfrac{44}{147}\)
\(x\div\dfrac{4}{7}=\dfrac{6}{7}-\dfrac{1}{3}\)
\(x\div\dfrac{4}{7}=\dfrac{11}{21}\)
\(x=\dfrac{11}{21}\times\dfrac{4}{7}\)
\(x=\dfrac{44}{147}\)
=>x:4/7=18/21-7/21=11/21
hay x=44/147
\(x:\dfrac{4}{7}=\dfrac{6}{7}-\dfrac{1}{3}\)
\(x:\dfrac{4}{7}=\dfrac{18}{21}-\dfrac{7}{21}\)
\(x:\dfrac{4}{7}=\dfrac{11}{21}\)
\(x=\dfrac{11}{21}\times\dfrac{4}{7}\)
\(x=\dfrac{44}{147}\)
HT
\(x:\dfrac{4}{7}=\dfrac{6}{7}-\dfrac{1}{3}\)
\(x:\dfrac{4}{7}=\dfrac{18}{21}-\dfrac{7}{21}\)
\(x:\dfrac{4}{7}=\dfrac{11}{21}\)
\(x=\dfrac{11}{21}X\dfrac{4}{7}\)
\(x=\dfrac{44}{147}\)